Pulling preK1 into a K-12 orbit: the evolution of preK in the age of standards. Issue 1 (2nd January 2017) - Graue, M. Elizabeth; Ryan, Sharon; Nocera, Amato; Northey, Kaitlin; Wilinski, Bethany
Abstract: We might call this decade the era of early childhood. In the US, federal and state governments invest in the creation of public pre-kindergarten (preK) programs and create standards that articulate goals for practice and benchmarks that can be used to evaluate success. How have these trends provided a context for the evolution of preK curriculum? In this paper, we analyze the enactment of preK policy in New Jersey, a highly regulated preK program and Wisconsin, a local control state. We argue that standards-based practice is evolving into accountability in public preK programs, where outcomes set parameters for planning and teachers and children are increasingly regulated. As preK is more closely affiliated with the K-12 sector (elementary and secondary), preK programs are subject to the logic of alignment, benchmarks and assessments. Even when early learning standards support child-centered approaches to curriculum they are overruled by accountability discourse.